MOVIMENTOS DA PROFISSIONALIZAÇÃO DOCENTE: DESENVOLVIMENTO PROFISSIONAL EM ENTREVISTAS NARRATIVAS - Munari, Keiti de Barros (2020)
When referring to teaching as a profession, we are faced with a constitutional movement that carries enchantments and disenchantments. In view of this context, we justify our research intentions by the concerns generated when trying to understand how the teaching professionalization movement takes place, considering the professional development of those who decide to remain in education. In this way, we aim to broaden understandings about being and being in the profession, through the perceptions of four teachers who lived, and live, teaching. It is our objective to elucidate the factors of permanence in the profession, reflecting on the teaching trajectories. We seek answers to the question: How have teachers perceived the constitution of their own professionalization in the face of their professional trajectories? With a qualitative approach, we used the narrative interview method (EN) to think about the cases of four teachers, who started their careers in Basic Education and work in private Higher Education. From a theoretical point of view, we base our study on the sociological perspective of Maurice Tardif and Richard Wittorski. We seek to establish dialogues between profession and professionalization, taking into account the development of teacher training, in its procedural and constitutive dimension, verifiable in the last three decades. Based on the results obtained, we found that the professional development of the researched teachers has its origin before the beginning of formal academic training, when they chose teaching, thus starting the movement of being teachers as they lived and live the teaching profession, preparing for being in the profession. Our reflections are based on two axes that we call motivational: a) influential factors in the external sphere (anchored in the relationships between peers, family and teacher teachers); and b) influential factors of the internal sphere (related to the personal charms of the teacher). When narrating their own professional trajectories, teachers take possession of what really motivates them to be and be a profession. Through the considerations presented, we take a new look at being in the profession, and, above all, about how the constitution of professionalization can be engendered by a processual and uninterrupted development. In this research, teachers present themselves assuming the protagonism granted by teaching, carrying for themselves the certainty that they are valuing education and improving their socio-professional status, regardless of their disenchantment. Thus, it remains for us to continue our studies on the constitution of teaching professionalism from new perspectives.